Konsep Recovery ( Pemulihan ) Sebelum, Selama Dan Setelah Kompetisi - Hayati, ; DR, ; M.kes, (Kepelatihan Olahraga, 2010)
Recovery is essential in improving your performance and also allowing you to perform your daily routine more efficiently. After athletic competition or a hard workout, it would seem that complete rest would be the best way to encourage recovery. There are many types of recovery according to the aim such as to remove lactic acid, to refill the energy and oxygen. Active recovery refers to engaging in low-intensity exercise after workouts. There are two forms of active recovery. One is during the cool-down phase immediately after a hard effort or workout. The second form of active recovery includes the days following a competition or other intense workout. Since the dawn of sports nutrition as a scientific discipline, one issue has consistently dominated practitioners attention the post-exercise window of opportunity for muscle recovery. Traditionally two nutrients have grabbed most of the muscle-recovery headlines: carbohydrate and protein. They were hell bent on recovering muscle glycogen as fast as possible so that performance in an event or training session occurring up to 24 hours later did not suffer. Protein was then added to the carbohydrate for two reasons: to improve glycogen accumulation beyond what could be achieved by consuming carbohydrate alone, to stimulate muscle protein synthesis.